2004
DOI: 10.1210/en.2004-0219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background (C57BL/6J Versus FVB/N) Strongly Influences the Severity of Diabetes and Insulin Resistance in ob/ob Mice

Abstract: We studied the effects of genetic background on the phenotype of ob/ob mice, a model of severe obesity, insulin resistance, and diabetes caused by leptin deficiency. Despite a comparable degree of obesity and hyperinsulinemia, C57BL/6J ob/ob mice had much milder hyperglycemia and, surprisingly, normal circulating adiponectin levels despite still-prominent signs of insulin resistance. Hyperinsulinemic-euglycemic clamp revealed relatively less whole-body and muscle insulin resistance in C57BL/6J ob/ob mice, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 37 publications
9
140
1
Order By: Relevance
“…Moreover, a number of genetic modifications leading to diabetes show diminished or no effect in this strain. 77 Mouse strains differ in their vascular response to diabetes and hyperlipidemia. Kunjathoor et al 78 assessed atherosclerosis in several strains of STZ-treated and cholic acidcontaining (Paigen) diet fed mice.…”
Section: Do Mouse Models Reproduce the Relationship Between Diabetes mentioning
confidence: 99%
“…Moreover, a number of genetic modifications leading to diabetes show diminished or no effect in this strain. 77 Mouse strains differ in their vascular response to diabetes and hyperlipidemia. Kunjathoor et al 78 assessed atherosclerosis in several strains of STZ-treated and cholic acidcontaining (Paigen) diet fed mice.…”
Section: Do Mouse Models Reproduce the Relationship Between Diabetes mentioning
confidence: 99%
“…Highly augmented serum levels of triglycerides, free fatty acids, oxidised lipoproteins, insulin and glucose are the pathophysiological consequences in obese persons. 10 In ob/ob mice, increase of these serum factors is associated with mild diabetes in the ob/ob mouse 11,12 and with excessively accumulated lipid droplets in cells of follicles and of the ovarian cortex. 8,13 The striking intraovarian lipogenesis is probably responsible for mitochondrial dysfunction with the augmented release of reactive oxygen species (ROS) leading to oxidative stress and cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin (Acrp30) is synthesized and secreted exclusively by adipocytes (16), and many studies have shown that high levels of adiponectin are associated with insulin sensitivity whereas low levels are found in insulin resistance (8,9,17). Furthermore, direct experiments have demonstrated that adiponectin can mediate insulin-sensitizing effects, most likely by activating AMP-activated protein kinase (AMPK).…”
mentioning
confidence: 99%